Model Manajemen Jaringan Sistem Kemitraan Dalam Pengembangan SLTP Daerah Terpencil - Ismail Tolla (Universitas Negeri Malang, 2016)
This study is intended to develop a model of Junior High School which can accommodate the teaching-learning needs of SLTP located in a remote area. The model is intended to be one which best utilizes the infrastructure and social resources or potential of the area. This study purposively selected the village of Leling in the sub-district of Kalumpang, Mamuju, South Celebes as the setting to carry out the exploration and action. The exploratory activities show that the selected area has the necessary resources to implement the model of SLTP using web-partnership management. This web-partnership management promotes the potential of the area so that the related parties are engaged in planning, implementing, and controlling the educational programs to achieve their shared goals. The model development activities realize the model consisting of organizational structure in the form of web the school elements or units of which, to reach the student home-base, are headed by a school associate principals. Within the context of village, the school associate principals are autonomous in their activities. Even though the model is established in view of maximizing the potential of remote areas, the model can also be transferred to different and not necessarily remote areas